2011
DOI: 10.1007/s12223-011-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbial properties of soil aggregates created by earthworms and other factors: spherical and prismatic soil aggregates from unreclaimed post-mining sites

Abstract: Soil aggregates between 2 and 5 mm from 35- and 45-year-old unreclaimed post-mining sites near Sokolov (Czech Republic) were divided into two groups: spherical and prismatic. X-ray tomography indicated that prismatic aggregates consisted of fragments of claystone bonded together by amorphous clay and roots while spherical aggregates consisted of a clay matrix and organic fragments of various sizes. Prismatic aggregates were presumed to be formed by plant roots and physical processes during weathering of Tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…This content of fossil organic matter is highly variable. Frouz et al (2011a) reported a range between 2.5 and 11.2 % of fossil C. Variation in fossil organic matter can cause variation in content of aliphatic components observed between our sites.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…This content of fossil organic matter is highly variable. Frouz et al (2011a) reported a range between 2.5 and 11.2 % of fossil C. Variation in fossil organic matter can cause variation in content of aliphatic components observed between our sites.…”
Section: Discussionmentioning
confidence: 59%
“…Difference in spectra can be partly caused by presence of Fe+ ions derived from siderite, which was abundant in the spoil material and may have affected the spectra by affecting phase coherence. We suspect, however, that data from the youngest reclaimed site were unusual because most of the organic matter at that site was derived from fossil kerogen, which is characteristically dominated by its aliphatic component (Krıbek et al 1998;Frouz et al 2011a). This content of fossil organic matter is highly variable.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations